Drivers of change to mountain sustainability in the Hindu Kush Himalaya - Wang, Yanfen; Wu, Ning; Kunze, Clemens; Long, Ruijun; Perlik, Manfred; Pandey, Abhimanyu (The Hindu Kush Himalaya assessment, 2019)
Many challenges for sustainability are related to weak governance, natural resource overexploitation, environmental degradation, certain aspects of unregulated or rapid urbanization, and loss of traditional culture.
Gesehen am 08.08.2024